Comparative perspectives of criminal procedure - Peristeridou, Christina; Klip, Andre (Cambridge : Intersentia, 2024)
"Criminal procedure includes a variety of procedures concerning investigating, adjudicating and sentencing suspects. The criminal justice system encompasses several actors and institutions and they all have their own specific role. Whereas criminal justice systems may differ greatly, many of the issues they face are the same. This poses questions such as under which conditions may investigations take place? What conclusions can be drawn from the collected evidence? What should happen if such rules are not respected? In addition, criminal procedure empowers citizens with rights in their relation to the state. How criminal justice is organised and the design of criminal procedure depends on the legal system in question: each has its own history, institutions and actors, principles, values and ways of organising state power to respond to criminal offences."--
Keywords: Criminal procedure; Criminal justice